The Reform of Equalization Payments - Dan Usher (Queen's University, Department of Economics, 2007)
A reasonable and fair interpretation of the mandate for equalization payments in Section 36(2) of the Canadian Constitution differs from the present equalization formula in these respects: Transfers to the poorer provinces would be financed by transfers from the richer provinces rather than from the Federal government. Entitlement to equalization payments would depend on provincial income rather than upon a tax-by-tax comparison of the provinces' many tax bases. For this comparison, provincial income would include revenue accruing directly to the provincial governments as well as private income of the residents of the province. Compensation would be made for the exemption of provincial resource revenue from Federal income tax. The most pronounced effect of these proposals would be to transfer the greater burden of equalization payments from Ontario to Alberta which is now, by far, the richest province.
Keywords: H77; H72; 330; Equilization; Federal-provincial transfers; Föderalismus; Länderfinanzen; Finanzausgleich; Kanada